ATM 2020
DOI: 10.20937/atm.52640
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the WRF model with different physical parameterizations in the precipitation simulation of the state of Puebla

Abstract: En México, las intensas lluvias generadas por ciclones tropicales, frentes fríos y sistemas convectivos de mesoescala pueden causar inundaciones y deslaves, los cuales provocan daños a los sectores sociales, de servicios, económicos y financieros, entre otros, y dejan a la población con menos recursos y en mayor vulnerabilidad. Dado este escenario, el tema de la prevención de desastres tiene relevancia en la agenda de protección civil, en la cual se reconoce que es indispensable establecer estrategias y progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This good correlation is verified through the Pearson correlation coefficient, which obtained a value of 0.92 at the Goiatins station and 0.84 at the Itacajá station. These values, considering other works presented in the literature that evaluated the performance of precipitation simulations using the WRF model [10,12,13], are considered very good.…”
Section: International Symposium On Innovation and Technology (Siintec)supporting
confidence: 61%
See 2 more Smart Citations
“…This good correlation is verified through the Pearson correlation coefficient, which obtained a value of 0.92 at the Goiatins station and 0.84 at the Itacajá station. These values, considering other works presented in the literature that evaluated the performance of precipitation simulations using the WRF model [10,12,13], are considered very good.…”
Section: International Symposium On Innovation and Technology (Siintec)supporting
confidence: 61%
“…One Planet, one Ocean and one Health -2021 The analysis between the observed and simulated data was done graphically and with some statistical indices, named: the correlation coefficient R, the root mean square error (RMSE), and the BIAS estimator, which are widely used to evaluate forecast models [ 10].…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] used the output from the WRF model (over the upper-Jordan River basin) as forcing to run the Hydrological Model for Karst Environment (HYMKE). Similar experiments were set in different areas [20][21][22][23], and the authors showed that the precipitation estimates with WRF are able to reproduce the spatial distribution of precipitation, but may underestimate the magnitude of the heavy precipitation events when compared to rain gauges or global observation datasets.…”
Section: Introductionmentioning
confidence: 99%